Social and Cultural Constraints on Football Player Development in Stockholm: Influencing Skill, Learning, and Wellbeing - Vaughan, James; Mallett, Clifford J.; Potrac, Paul; Woods, Carl; O'Sullivan, Mark; Davids, Keith (Frontiers in Sports and Active Living, 2022)
In this paper, we consider how youth sport and (talent) development environments have adapted to, and are constrained by, social and cultural forces. Empirical evidence from an 18-month ethnographic case study highlights how social and cultural constraints influence the skill development and psychological wellbeing of young football players. We utilized novel ways of knowing (i.e., epistemologies) coupled to ecological frameworks (e.g., the theory of ecological dynamics and the skilled intentionality framework). A transdisciplinary inquiry was used to demonstrate that the values which athletes embody in sports are constrained by the character of the social institutions (sport club, governing body) and the social order (culture) in which they live. The constraining character of an athlete (talent) development environment is captured using ethnographic methods that illuminate a sociocultural value-directedness toward individual competition. The discussion highlights how an emphasis on individual competition overshadows opportunities (e.g., shared, and nested affordances) for collective collaboration in football. Conceptually, we argue that these findings characterize how a dominating sociocultural constraint may negatively influence the skill development, in game performance, and psychological wellbeing (via performance anxiety) of young football players in Stockholm. Viewing cultures and performance environments as embedded complex adaptive systems, with human development as ecological, it becomes clear that microenvironments and embedded relations underpinning athlete development in high performance sports organizations are deeply susceptible to broad cultural trends toward neoliberalism and competitive individualism. Weaving transdisciplinary lines of inquiry, it is clarified how a value directedness toward individual competition may overshadow collective collaboration, not only amplifying socio-cognitive related issues (anxiety, depression, emotional disturbances) but simultaneously limiting perceptual learning, skill development, team coordination and performance at all levels in a sport organization.